Impacts of systemic inflammation response index on the prognosis of patients with ischemic heart failure after percutaneous coronary intervention - Ma, Meishi; Wu, Kang; Sun, Tienan; Huang, Xin; Zhang, Biyang; Chen, Zheng; Zhao, Zehao; Zhao, Jiajian; Zhou, Yujie (Frontiers in Immunology, 2024)
Background: As a new inflammatory marker, the systemic inflammation response index (SIRI) has been demonstrated to be connected to prognoses of cardiovascular diseases. Investigating the prognostic impact of SIRI in individuals having ischemic heart failure (IHF) following percutaneous coronary intervention (PCI) is the goal of this research. Methods: The research involved 1963 IHF individuals who received PCI, with a 36-month follow-up duration. Based on the SIRI quartiles, all patients were classified into four groups. The major adverse cardiovascular events (MACE) were the primary outcome. Every element of the main endpoint appeared in the secondary endpoints: all-cause mortality, non-fatal myocardial infarction (MI), and any revascularization. The Kaplan-Meier survival analysis was conducted to assess the incidence of endpoints across four groups. The multivariate Cox proportional hazards analysis has confirmed the independent impact of SIRI on both primary and secondary endpoints. The restricted cubic spline (RCS) was used to assess the non-linear association between SIRI and the endpoints. Subgroup analysis was played to confirm the implications of SIRI on MACE in different subgroups. Result: The main outcome was much more common in those with higher SIRI. The Kaplan-Meier curve was another tool that was accustomed to confirm the favorable connection between SIRI and MACE. SIRI was individually connected to a higher chance of the main outcome according to multivariate analyses, whether or not SIRI was a constant [SIRI, per one‑unit increase, hazard ratio (HR) 1.04, 95% confidence interval (95% CI) 1.01-1.07, p=0.003] or categorical variable [quartile of SIRI, the HR (95% CI) values for quartile 4 was 1.88 (1.47-2.42), p< 0.001, with quartile 1 as a reference]. RCS demonstrated the hazard of the primary endpoint and secondary endpoints increased as SIRI increased in general. And the non-linear association of SIRI with the risk of MACE and any revascularization (Non-linear P<0.001) was observed. Subgroup analysis confirmed the increased risk of MACE with elevated SIRI in subgroup of New York Heart Association (NYHA) class III-IV (P for interaction=0.005). Conclusion: In patients with IHF undertaking PCI, increased SIRI was a risk factor for MACE independent of other factors.